2023
DOI: 10.1021/jacs.2c10749
|View full text |Cite
|
Sign up to set email alerts
|

A Telomerase-Activated Magnetic Resonance Imaging Probe for Consecutively Monitoring Tumor Growth Kinetics and In Situ Screening Inhibitors

Abstract: Telomerase has long been considered as a biomarker for cancer diagnosis and a therapeutic target for drug discovery. Detecting telomerase activity in vivo could provide more direct information of tumor progression and response to drug treatment, which, however, is hampered by the lack of an effective probe that can generate an output signal without a tissue penetration depth limit. In this study, using the principle of distance-dependent magnetic resonance tuning, we constructed a telomerase-activated magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…22,23 Therefore, there has been a lot of work in recent years to involve the specific binding of telomerase to specific sequences as a recognition modality in the design of biosensors for telomerase activity detection. Yang's group 39 has constructed a telomerase-activated MRI probe, achieving the monitoring of telomerase activity in vivo. The probe displaces down the paramagnetic complexlabeled NA strand through recognition and extension of the primer by telomerase, thus enabling a distancedependent shift of the MRI signal from off to on.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Therefore, there has been a lot of work in recent years to involve the specific binding of telomerase to specific sequences as a recognition modality in the design of biosensors for telomerase activity detection. Yang's group 39 has constructed a telomerase-activated MRI probe, achieving the monitoring of telomerase activity in vivo. The probe displaces down the paramagnetic complexlabeled NA strand through recognition and extension of the primer by telomerase, thus enabling a distancedependent shift of the MRI signal from off to on.…”
Section: Othersmentioning
confidence: 99%
“…By modifying DNA strands with NIR fluorophores/quencher pair, they have achieved an effective combination of the activatable properties of NA probes with high resolution at a deep penetration depth of PA imaging. In addition to PET and PA imaging, Wang's group 39 developed a telomerase‐activated magnetic resonance (MR) imaging probe for telomerase detection in vivo. Paramagnetic Gd‐DOTA ((Gd(III) 1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tet‐raacetic acid) complexes was conjugated to the oligonucleotides, which hybridized with anchor DNA.…”
Section: In Vivo Nucleic Acid Biosensorsmentioning
confidence: 99%
“…It was also shown that TBA and its TBA535 analogue exhibit antimotility properties [5] . To improve the therapeutic and diagnostic potential of aptamers, their complexation with various types of nanoparticles is advantageous [6–9] …”
Section: Introductionmentioning
confidence: 99%
“…[5] To improve the therapeutic and diagnostic potential of aptamers, their complexation with various types of nanoparticles is advantageous. [6][7][8][9] Dendrimers represent a synthetic group of polymer nanoparticles with an unique well defined radially branched structure being highly investigated as non-viral vectors and drug delivery carriers. [10] For these purposes, various types of dendrimers have been synthetized, such as carbosilane dendrimers, [11,12] polylysine dendrimers, [13] phosphorus-containing dendrimers [14] as well as commercially available polyamidoamine (PAMAM) dendrimers.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite advances in diagnostic and therapeutic technologies, as well as clinical treatments, the incidence of cancer continues to rise and the mortality rates still remain at high levels. [2][3][4][5] Currently, chemotherapy is widely used in clinical treatment; however, many chemotherapeutic drugs fail to specifically target cancer cells and tissues or exhibit low cellular uptake, resulting in high toxicity to normal tissues. 6,7 As a result, the dosage of drugs that can be used in clinical treatment is limited.…”
mentioning
confidence: 99%